Personal Data Protection Of Predictive Analytics In Online Shopping: From Malaysian Legal Perspective - Muhammad Afdal bin Noor Azman; Muhammad Nizam Awang (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
Lack of legal coverage over personal data protection in predictive analytics of online shopping is a huge concern. This would expose their personal data to misuse whether for legal or illegal purposes especially in online shopping, hence cause privacy intrusion. It was argued that the information used during the processes of predictive analysis will not infer any particular person, thus deprive their privacy of life. Study shows that, the latest Personal Data Protection Act (PDPA) 2010 does not cover the usage of personal information under predictive analytics processes. This shows the lacuna or the gap of the gazetted law. Besides, a statistic in September 2019 reported that more than 26 million of Malaysians are using internet, and the data from GlobalWebIndex also shows that 80 percent users between the ages of 16 and 64 are using online shopping platforms. The main aim of this paper is to propose a number of preliminary suggestions to ensure that the personal data gathered from online shopping which were used in predictive analytics are covered under the PDPA 2010 with reference and comparison from the leading jurisdictions such as United Kingdom and United States of America, and also from Asian Pacific countries such as Hong Kong, New Zealand and Australia. This paper focuses on the online shopping platforms because the personal data can be easily collected and exposed to many users compared to the collected data in other type of businesses. The most testing question here is whether the data used in the predictive analytics of the online shopping is within the ambit of personal data protection under PDPA 2010 in particular, and under the General Data Protection Regulation (GDPR) in general. In this context, the PDPA 2010 only covers the personal information from the commercial transaction with exception to, Federal and State Governments, as well as the personal data processed outside Malaysia. Furthermore, predictive analytics is commonly defined as an area of statistics that deals with extracting information from data and using it to predict trends, behaviour patterns, and etc. To achieve the objective of this paper, the study will be conducted through literature review which is qualitative in nature. A recent study shows that some countries such as Australia does consider a set of individual information used in predictive analytics deemed as personal data and should be protected under the law. Thus, it is recommended that the personal data involved in the predictive analytics collected from the online shopping to be covered under the ambit of PDPA 2010